2018
DOI: 10.1111/coa.13175
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of survival factors in rhino‐orbital‐cerebral mucormycosis—has anything changed in the past 20 years?

Abstract: Although overall survival rates have not improved, survival in patients with renal disease were better, potentially due to the introduction of liposomal amphotericin B which is less nephrotoxic. Prompt recognition of ROCM, reversal of predisposing co-morbidities and aggressive medical treatment remain the cornerstone of managing this highly aggressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
108
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 135 publications
(133 reference statements)
8
108
0
10
Order By: Relevance
“…In contrast, similar mortality rates 5,6 or even better survival of non‐diabetic ROCM 10 have been reported in other studies. Based on recent meta‐analysis, survival rates in non‐diabetics had improved to 50% especially in patients with renal failure and leukaemia 5 . Introduction of less toxic antifungal agents such as liposomal amphotericin B into routine clinical practice and improved diagnostic tests and therapies of malignancies were possible causes 5 .…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In contrast, similar mortality rates 5,6 or even better survival of non‐diabetic ROCM 10 have been reported in other studies. Based on recent meta‐analysis, survival rates in non‐diabetics had improved to 50% especially in patients with renal failure and leukaemia 5 . Introduction of less toxic antifungal agents such as liposomal amphotericin B into routine clinical practice and improved diagnostic tests and therapies of malignancies were possible causes 5 .…”
Section: Discussionsupporting
confidence: 80%
“…Some studies 7,9,20 have reported a higher mortality rate in non‐diabetics which could be because of more debilitated nature of the patients as well as the reversibility of the diabetic immune dysfunction 7,9,20 . In contrast, similar mortality rates 5,6 or even better survival of non‐diabetic ROCM 10 have been reported in other studies. Based on recent meta‐analysis, survival rates in non‐diabetics had improved to 50% especially in patients with renal failure and leukaemia 5 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations